Perfect shot : a thriller - Urszenyi, Steve (Minotaur Books, 2023)
"A former Army sniper must fall back on her Special Ops skills when a friend's death uncovers a global nuclear threat, in this electrifying new series featuring Special Agent Alexandra Martel. Special Agent Alexandra Martel has put her days on the battlefield behind her. Charming and disarming, relentless and lethal, she earned a reputation as one of the most renowned and decorated Army snipers in the service before stepping away. But when Alex, now an FBI special agent on loan to Interpol, learns that an old friend, an MI5 officer, has been killed under mysterious circumstances, she's pulled back into the dangerous world she left behind: a world where some people fear her, some want to recruit her, and everyone seems to want her dead. Following a trail of clues left behind by the dead woman, Alex pieces together a terrifying conspiracy that only escalates when a nuclear warhead goes missing. Dodging death at every turn, she reluctantly joins forces with a CIA agent, but he has plans of his own for her-and will stop at nothing to achieve them. Chasing the truth through the streets of London and bustling Turkish markets to the underbelly of Paris, Alex is unrelenting in her pursuit of justice. But as the clock ticks down and the world edges closer to doom, she must fall back on her Special Ops skills to stop the unthinkable. She thought her life as a sniper was over-but with stakes this high, she must use whatever means necessary to render the world safe"--